Annual Report on Exchange Arrangements and Exchange Restrictions 1996. (Annual Report on Exchange Arrangements and Exchange Restrictions, 1996)
Published since 1950, this authoritative annual reference is based upon a unique IMF database that tracks exchange and trade arrangements for the 187 IMF member countries, along with Hong Kong SAR, Aruba, and Curacao and St Maarten. The Annual Report on Exchange Arrangements and Exchange Restrictions (AREAER) draws together information on exchange measures in place, the structure and setting of exchange rates, arrangements for payments and receipts, procedures for resident and nonresident accounts, controls on capital transactions, and provisions specific to the financial sector. The data are presented in a clear, easy-to-read tabular format. A summary table allows for simple cross-country comparisons of key features of their exchange and trade regimes. The report's introduction summarizes recent global trends and developments.